Comparative analysis of the potential effect of phase I therapy on gingival crevicular fluid myeloperoxidase levels in non-diabetic and diabetic patients with periodontitis - Hakan Develioğlu; Hakan Özdemir; Hüseyin Aydın; Kaya Eren; Nermin Yamalık (Cumhuriyet University, 2014)
Objectives: To evaluate the effect of periodontal therapy on clinical parameters as well as on myeloperoxidase (MPO) activity in the gingival crevicular fluid (GCF) of patients with type 2 diabetes mellitus and of systemically healthy individuals.Materials and Methods: 24 type 2 DM patients subjects, and 21 systemically healthy individuals, both groups with chronic periodontitis, and systemically and periodontally healthy individuals were enrolled. Periodontal clinical parameters, namely periodontal probing depth (PD), plaque index (PI), gingival index (GI), clinical attachment level (CAL), and gingival bleeding time index (GBI), as well as GCF MPO activity, were assessed before and 3 months after non-surgical periodontal therapy. GCF enzyme activity was spectrophotometrically analyzed. Possible correlation between clinical periodontal status and MPO activity was also evaluated.Results: Despite the relatively stable clinical measures and GCF MPO content in the periodontally-healthy subjects, the clinical periodontal status improved, as significant reductions were observed in all of the clinical parameters in periodontitis patients with and without diabetes (p<0.05). GCF MPO activity presented with significant reductions in both of the periodontally-diseased groups after phase I treatment (p<0.05), however it could not reach to the level of periodontal health (p<0.05).Conclusions: Periodontal inflammation is likely to play the major role in the higher MPO activity observed at diseased sites, while diabetes mellitus do not seem to further increase the production of this enzyme. Periodontal treatment can provide successful improvement in clinical periodontal parameters and reduction in enzyme profile of GCF in diabetics.